Hubungan Tingkat Sesak Nafas dengan Kualitas Hidup Pasien Paru Obstruktif Kronik (PPOK) di Ruang Rawat Inap Paru RSUD Cut Nyak Dhien Meulaboh - Rianita Silvia Pandia; Rizaty Mahira; Revina Pandu Inata Hotmauli; Maysarah Maysarah; Darnia Zalukhu; Tiarnida Nababan (Journal of Educational Innovation and Public Health, 2026)
Chronic Obstructive Pulmonary Disease is a chronic respiratory disease characterized by progressive and not fully reversible airflow limitation. Dyspnea is the primary symptom experienced by COPD patients and significantly affects their quality of life, especially among those hospitalized. This condition may lead to activity limitation, psychological distress, and decreased social functioning. This study aimed to determine the relationship between the level of dyspnea and the quality of life of COPD patients in the pulmonary inpatient ward of Cut Nyak Dhien General Hospital Meulaboh. This study employed an analytical design with a cross-sectional approach. The sample consisted of hospitalized COPD patients selected using purposive sampling. Dyspnea severity was measured using the Modified Medical Research Council (mMRC) scale, while quality of life was assessed using the St. George’s Respiratory Questionnaire (SGRQ). Data were analyzed using the Spearman correlation test to determine the relationship between variables.The results showed that most respondents experienced moderate to severe dyspnea and had poor quality of life. Statistical analysis revealed a significant relationship between dyspnea level and quality of life (p < 0.05) with a negative correlation.In conclusion, there is a significant relationship between dyspnea severity and quality of life in COPD patients, where higher dyspnea levels are associated with lower quality of life.